Bystander society : conformity and complicity in Nazi Germany and the Holocaust - Fulbrook, Mary 1951- (Oxford University Press, 2023)
"Bystander Society provides an overview of the notion of by standing within Nazi Germany. It details the social conditions before and during the Nazi regime in Germany that eventually facilitated a series of mass murders. The role of ordinary Germans enabled the emergence of Nazisms and its subsequent exclusion, persecution, and extermination of people. The creation of a bystander society coincides with how most Germans were unable to act or developed growing indifference to the fate of non-Aryans, Jews, and people considered outside the Volksgemeinschaft. Bystander Society highlights the significance of changing social and political circumstances during the Nazi regime by referencing first-hand narratives of primary victims and people who stayed on the sidelines to avoid violence"--